Marmee : [large type] a novel - Miller, Sarah, 1979- (Harper Large Print, an imprint of HarperCollinsPublishers, 2022)
In 1861, war is raging in the South, but in Concord, Massachusetts, Margaret March has her own battles to fight. With her husband serving as an army chaplain, the comfort and security of Margaret's four daughters, Meg, Jo, Beth, and Amy, now rest on her shoulders alone. Money is tight and every month, her husband sends less and less of his salary with no explanation. Worst of all, Margaret harbors the secret that these financial hardships are largely her fault, thanks to a disastrous mistake made over a decade ago which wiped out her family's fortune and snatched away her daughters' chances for the education they deserve. Yet even with all that weighs upon her, Margaret longs to do more, for the war effort, for the poor, for the cause of abolition, and most of all, for her daughters. Living by her watchwords, "Hope and keep busy," she fills her days with humdrum charity work to keep her worries at bay. All of that is interrupted when Margaret receives a telegram from the War Department, summoning her to her husband's bedside in Washington, D.C. While she is away, her daughter Beth falls dangerously ill, forcing Margaret to confront the possibility that the price of her own generosity toward others may be her daughter's life.